Forgotten family members: the importance of siblings in early psychosis. Issue 3 (27th June 2013) - Bowman, Siann; Alvarez‐Jimenez, Mario; Wade, Darryl; McGorry, Patrick; Howie, Linsey
Abstract Objective This paper reviews the evidence on the significance of sibling inclusion in family interventions and support during early psychosis. Method This narrative review presents the current research related to the importance of family work during early psychosis, the needs and developmental significance of siblings during adolescence and early adulthood, the protective effects of sibling relationships, and the characteristics of early psychosis relevant to the sibling experience. It will also review the evidence of the sibling experience in chronic physical illness and disability, as well as long‐term psychotic illness. Conclusions Despite the evidence that working with families is important during early psychosis, siblings have been largely ignored. Siblings are an important reciprocal relationship of long duration. They play an important role in development during adolescence and early adulthood. These relationships may be an underutilized protective factor due to their inherent benefits and social support. Developmental theories imply that early psychosis could negatively impact the sibling relationship and their quality of life, effecting personality development and health outcomes. The evidence shows that adolescent physical illness or disability has a significantly negative impact on the sibling's quality of life and increases the risk for the onset of mental health issues. Long‐term psychotic illness also results in negative experiences for siblings. Current evidence shows that siblings in early psychosis experience psychological distress and changes in functional performance. Further research using standard measures is required to understand the impact early psychosis has on the sibling relationship and their quality of life.